The Shifting Use of Isrā’īlīyāt in Qur’anic Exegesis and Its Implications on The Comprehension of the Verses on Jālūt and Ṭālūt Story: A Critical Study of Indonesian Qur’anic Exegesis - Ghozali, Mahbub (UIN Sunan Kalijaga Yogyakarta, 2024)
This study focuses on the use of isrā’īlīyāt narratives in three pesantren-related Qur’anic exegesis in Indonesia. There have been many recent studies to explore the use of isrā'īlīyāt in exegesis, but the analysis on the use of isrā'īlīyāt narratives, its underlying factors, and its impact on exegesis has not been widely discussed. By limiting to examining the use of isrā'īlīyāt narratives in the stories of Jālūt and Ṭālūt, this study revealed a shift in the use of isrāīlīyāt from the validity aspect to the functional aspect. It also disclosed two functions of isrā'īlīyāt: the descriptive and medical functions. The descriptive function represents the moral content in the story of the Qur'an, which has an impact on the purpose of mentioning stories in the Qur’an as i'tibār (something to learning). The medical function, refers to the internal tendency of the interpreter to choose the story, and this function determines the pattern in the exegesis of narrative verses. The exegesis pattern in methodological studies is directed only at verses with legal and theological nuances, by excluding narrative verses.